Pengaruh Jarak Tanam Terhadap Pola Pertumbuhan Tanaman Sorgum Lokal Sumba (Watar Hammu Kiku Mbimbi) - Bulu, Lewi; Sudarma, I Made Adi; Pati, Denisius Umbu (JURNAL PETERNAKAN SABANA, 2025)
The utilization of sorghum biomass as animal feed from agricultural waste needs to be increased due to the lack of availability of animal feed due to the long dry season on Sumba Island. One alternative to increase sorghum productivity is to regulate the appropriate planting distance for the growth and production of sorghum plants. This study used a completely randomized design with 5 treatments and 3 replications where 1 replication had 18 planting holes so that there were 270 planting holes. The treatments given were P1 = planting distance 25 cm x 25 cm; P2 = planting distance 25 cm x 37.5 cm; P3 = planting distance 25 cm x 50 cm; P4 = planting distance 25 cm x 62.5 cm; and P5 = planting distance 25 cm x 75 cm. The variables observed were plant height and number of plants. The results of this study indicate that different planting distance treatments have a significant effect on the height of local sorghum plants where a closer planting distance (25x25) is able to provide a fairly higher plant height, while the number of growth shows good results in all treatments. It is concluded that local sorghum plants as animal feed can be planted at a closer planting distance to produce more optimal biomass production.